PKM PENGABDIAN MASYARAKAT BAHASA INGGRIS UNTUK ANAK USIA SEKOLAH MELALUI VIDEO ANIMASI PENGENALAN FAUNA DI BANJAR SIGARAN DESA SEDANG KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Introduction to fauna in English through animated videos is an effort to introduce the names of animals and their habitats orally and in writing. The purpose of this community engagement activity is to (1) imitate and pronounce the English names of animals according to the pictures, (2) match the English words with the animal pictures, and (3) connect the pictures with the written English words. The method used is socialisation and mentoring, by providing materials on the introduction of fauna in English through animated videos. The participants of this activity are 23 students from the 2nd and 3rd grades of SD Negeri 1 Sedang. The results of this activity are: (1) conducting field approaches and observations, (2) the team providing facilities such as material delivery, videos, gifts, and snacks in the form of biscuits and milk to the participants, (3) providing training through materials, games, and question-and-answer sessions, (4) evaluating the participants' understanding of the given materials. The observations and evaluations show that the participants have understood several English vocabulary words related to the names of animals and their habitats.